Model of Ventilation System Drive with Fuzzy Controller - Lisauskas, S.; Rinkevičienė, R. (Elektronika ir Elektrotechnika, 2010)
Simulation model of ventilation system with fuzzy controller is elaborated and considered. System comprises scalar control induction motor drive with Fuzzy controller and overpressure feedback. Overpressure error and derivative of error are assumed inputs of Fuzzy controller. Output, defined as control input of V/F block, produces input signal for discrete PWM generator. Simulation results of speed, electromagnetic torque, and motor phase current and overpressure error and its derivative are presented and considered.